2022
DOI: 10.1186/s12978-022-01434-6
|View full text |Cite|
|
Sign up to set email alerts
|

ASRHR in Ethiopia: reviewing progress over the last 20 years and looking ahead to the next 10 years

Abstract: Over the last two decades, improvements in Ethiopia’s socio-economic context, the prioritization of health and development in the national agenda, and ambitious national health and development policies and programmes have contributed to improvements in the living standards and well-being of the population as a whole including adolescents. Improvements have occurred in a number of health outcomes, for example reduction in levels of harmful practices i.e., in child marriage and female genital mutilation/cutting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The commentaries in this supplement highlight facilitators and barriers to achieving the goals of these strategic plans. Akwara et al and Admassu et al advocate for a broad policy framework, including expanding enabling laws, policies, and funding to ensure that quality SRH services are adequately extended to reach the youth population [ 12 , 33 ]. The current, and third, AY health strategy provides key parameters for advancing AY health: it sets key objectives and highlights leadership and accountability, including youth leadership and engagement, as critical strategies to meet the government’s FP2030 commitment to improve access to AYSRH-responsive services and to achieve better AYSRH outcomes [ 6 , 33 ].…”
Section: Looking To the Futurementioning
confidence: 99%
See 1 more Smart Citation
“…The commentaries in this supplement highlight facilitators and barriers to achieving the goals of these strategic plans. Akwara et al and Admassu et al advocate for a broad policy framework, including expanding enabling laws, policies, and funding to ensure that quality SRH services are adequately extended to reach the youth population [ 12 , 33 ]. The current, and third, AY health strategy provides key parameters for advancing AY health: it sets key objectives and highlights leadership and accountability, including youth leadership and engagement, as critical strategies to meet the government’s FP2030 commitment to improve access to AYSRH-responsive services and to achieve better AYSRH outcomes [ 6 , 33 ].…”
Section: Looking To the Futurementioning
confidence: 99%
“…The following section presents research focused on the adolescent and youth population—exploring the rapidly changing environment and social norms that affect their attitudes and behaviors and guide the debut and early stages of their reproductive lives. Akwara et al review the progress made on adolescent reproductive health indicators over the past two decades [ 12 ]. Erulkar and Lindstrom et al provide evidence on how these changing norms impact the ages of first marriage and first sex [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“… 29 , 30 Moreover, gender and power disparities, as evidenced by high rates of child marriage, IPV, and female genital cutting, 27 may impede women’s access to and use of contraception. While Ethiopia has made considerable progress in improving access to reproductive health services nationally, regional disparities persist among several key reproductive health outcomes; 31 , 32 specifically, 16% of women in rural areas have an unmet need for contraception, compared to only 8% of urban women. 26 There is further variation in access to reproductive health services across regions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“… 32 , 33 Regional disparities are compounded with high rates of child marriage, IPV, and female genital mutilation. 27 , 31 The percentage of women aged 15–19 who have begun childbearing ranges from 23% in Afar to 3% in Addis Ababa. 27 Contextual data is necessary to understand reasons for contraceptive non-use and the potential role of the partner in method selection, uptake, and continuation in order to ensure human rights components of autonomy and self-determination are upheld within Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…After publication of this article [1], the authors reported that the author name 'Venkatraman Chandra Mouli' was incorrectly written as 'Venkatraman Chandra Moulli' . Also, the author name 'Lamessa Oljira' was incorrectly written as 'Lamessa Oljiira' .…”
mentioning
confidence: 99%